Beyond Function: Imagination as Semi-Determination - Sabolius, Kristupas (Problemos, 2021)
The article raises the hypothesis that the activity of imagination cannot be fully described by a functional description. To this end, two positions are analyzed: the philosophy of Cornelius Castoriadis, who emphasizes social imaginary and radical imagination, is juxtaposed with Gilbert Simondon’s theory of cyclic and genetic images. Castoriadis’s consideration reveals the specific character of indeterminacy, found in the work of imagination, which enables the coexistence of contradictions in psyche. Based on this reading I propose to perceive imagination through a semi-deterministic take. Whilst it is also possible to see an effort to overcome functional determination in Simondon’s theory, the latter also offers a way to interpret the imagination beyond the anthropological realm. The image performs as mutual potential between organisms and their milieus, and this relationality is never fully determined, but rather semi-determined. Thus, by providing the tools for rethinking of determination and functionality, the juxtaposition of Castoriadis and Simondon enables to speculate on the need of a possible the concept of sociobiological imagination.
Keywords: imagination; the imaginary; function; determination; milieu